World Association for Bronchology and Interventional Pulmonology (WABIP) guidelines on airway stenting for malignant central airway obstruction - Chaddha, Udit; Agrawal, Abhinav; Kurman, Jonathan; Ortiz-Comino, Rosamaria; Dutau, Herve; Freitag, Lutz; Trisolini, Rocco; Dooms, Christophe; Zuccatosta, Lina; Gasparini, Stefano; Herth, Felix; Saka, Hideo; et al. (Respirology, 2024)
Malignant Central Airway Obstruction (MCAO) encompasses significant and symptomatic narrowing of the central airways that can occur due to primary lung cancer or metastatic disease. Therapeutic bronchoscopy is associated with high technical success and symptomatic relief and includes a wide range of airway interventions including airway stents. Published literature suggests that stenting practices vary significantly across the world primarily due to lack of guidance. This document aims to address this knowledge gap by addressing relevant questions related to airway stenting in MCAO. An international group of 17 experts from 17 institutions across 11 countries with experience in using airway stenting for MCAO was convened as part of this guideline statement through the World Association for Bronchology and Interventional Pulmonology (WABIP). We performed a literature and internet search for reports addressing six clinically relevant questions. This guideline statement, consisting of recommendations addressing these six PICO questions, was formulated by a systematic and rigorous process involving the evaluation of published evidence, augmented with expert experience when necessary. Panel members participated in the development of the final recommendations using the modified Delphi technique.
Online veröffentlicht: 29. Mai 2024
Gesehen am 11.02.2025